Sosialisasi Penguatan Peran Pemilih Pemula menuju Pilkada Yang Berdemokrasi - Supriyanto; Andhi Nur Rahmadi; Imam Sucahyo; Verto Septiandika; Reny Candra Dewi; Mastina Maksin (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The existence of the state is inseparable from political activities. All parties have a role in state politics. Including the younger generation who have a role in politics, such as becoming first-time voters in central and regional elections. The role of novice voters who actively participate in elections shows the success of democracy in a country. However, the findings in the field are still many who do not understand about politics and the role of novice voters. This finding moved the service team to organize socialization to the younger generation. Service activities are carried out with a participatory action research (PAR) model. Service partners are aimed at students of the Faculty of Social and Political Sciences, Panca Marga University in the second and fourth semesters. The service activity with the theme "Socialization of Strengthening the Role of Beginner Voters towards Democratic Pilkada was attended by 40 partners. Socialization activities show indicators of the success of program achievements. The results of monitoring and evaluation on the results of the questionnaire show that the activity increases the understanding of partners in political literacy and the participation of novice voters in the Pilkada. All partners enthusiastically participated in the activity from beginning to end.